Nonvolatile CBRAM-crossbar-based 3-D-integrated hybrid memory for data retention - Wang, Yuhao (2014)
This paper explores the design of 3-D-integrated hybrid memory by conductive-bridge random-access-memory (CBRAM). Considering internal states, height, and radius of the conductive bridge of one CBRAM device, an accurate CBRAM device model is developed for CBRAM-crossbar-based nonvolatile memory design with efficient estimation of area, access time, and power. Based on this design platform, one 3-D-integrated hybrid memory is designed by stacking one tier of CBRAM-crossbar with tiers of static random access memory (SRAM) and dynamic random access memory (DRAM), where the tier of CBRAM-crossbar is deployed for data retention during power gating of SRAM/DRAM tiers. One corresponding block-level data retention is developed to only write back dirty data from SRAM/DRAM to CBRAM-crossbar. When compared with phase-change random-access-memory-based system-level data retention, our design achieves 11× faster data-migration speed and 10× less data-migration power. When compared with ferroelectric random-access-memory-based bit-level data retention, our design also achieves 17× smaller area and 56× smaller power under the same data-migration speed.